2023
DOI: 10.3390/biology12030424
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Response Evaluation of Human Foetal Osteoblast Cells within Engineered 3D-Printed Polylactic Acid Scaffolds

Abstract: Large bone defect treatments have always been one of the important challenges in clinical practice and created a huge demand for more efficacious regenerative approaches. The bone tissue engineering (BTE) approach offered a new alternative to conventional bone grafts, addressing all clinical needs. Over the past years, BTE research is focused on the study and realisation of new biomaterials, including 3D-printed supports to improve mechanical, structural and biological properties. Among these, polylactic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…As can be seen in Figure 8a-l, PLA-CD 5% scaffolds preserve the fluorescence property of CDs at every time point analyzed, suggesting their stability under physiological conditions and relevance in non-invasive tissue engineering monitoring applications. The data derived from both cell viability and morphological characterization analyses align with prior studies, indicating that PLA scaffolds exhibit the capability to support cell adhesion, growth, and proliferation [38]. Moreover, the incorporation of highly stable fluorescent CDs into a PLA polymer matrix offers a long-term non-invasive cell-scaffold interaction helpful in analyzing tissue regeneration kinetics [34].…”
Section: Of 17supporting
confidence: 75%
See 1 more Smart Citation
“…As can be seen in Figure 8a-l, PLA-CD 5% scaffolds preserve the fluorescence property of CDs at every time point analyzed, suggesting their stability under physiological conditions and relevance in non-invasive tissue engineering monitoring applications. The data derived from both cell viability and morphological characterization analyses align with prior studies, indicating that PLA scaffolds exhibit the capability to support cell adhesion, growth, and proliferation [38]. Moreover, the incorporation of highly stable fluorescent CDs into a PLA polymer matrix offers a long-term non-invasive cell-scaffold interaction helpful in analyzing tissue regeneration kinetics [34].…”
Section: Of 17supporting
confidence: 75%
“…both cell viability and morphological characterization analyses align with prior indicating that PLA scaffolds exhibit the capability to support cell adhesion, grow proliferation [38]. Moreover, the incorporation of highly stable fluorescent CD PLA polymer matrix offers a long-term non-invasive cell-scaffold interaction he analyzing tissue regeneration kinetics [34].…”
Section: Of 17supporting
confidence: 74%
“…(c) Synthetic polymers, including polystyrene, PLA, PGA, PCL, and polylactic-co-glycolic acid (PLGA), are often used, due to the possibility of regulating their mechanical properties, biodegradability, morphology, and structure during the fabrication process [64,65]. Recently, some in vitro studies have shown that 3D-printed PLA scaffolds are able to promote the adhesion, proliferation, and differentiation of osteoblast cells [66,67]. In another study, the osteoregenerative capability of a porous PLGA (P) scaffold combined with magnesium hydroxide (MH, M), bone-extracellular matrix (bECM, E), and bioactive polydeoxyribonucleotide (PDRN, P) (PMEP scaffold) was evaluated.…”
Section: Biomaterials For Bte Applicationsmentioning
confidence: 99%